The frequency of overweight and obesity occurrence among Polish children (age 6–7 years) in relation to the place of residence, the education level of parents and the number children in the family - Markowska, Małgorzata; Przychodni, Agnieszka Monika; Nowak-Starz, Grażyna; Cieśla, Elżbieta (Anthropological Review, 2017)
This study sought to evaluate the number of those overweight and the rate of obesity among 6- and 7-year-olds living in Poland with regard to their place of residence, the parental level of education and the number of children in the family. The analysis was based on a survey of 64 544 children (33 051 boys and 31 493 girls) living in Poland. Overweight and obesity were defined based on body mass index (BMI) using the IOTF cut-off points. To evaluate the rates of overweight and obesity occurrence in children with regard to family socio-economic status, parental level of education, the number of children in the family, and the place of residence (divided into city and village) was used. ‘Only children’ were the most likely group to be overweight or obese. These children were twice as likely to be obese as their peers living in families with four or more children. Overweight and obesity occurred more often amongst children living in cities rather than those living in rural areas. Moreover, these conditions were more frequent among children whose parents had higher levels of education. The most significant predictors of childhood overweight and obesity were the number of children in the family and the educational level of the mother.